An overview of the extant genera and subgenera of the order Scolopendromorpha (Chilopoda): a new identification key and updated diagnoses - Schileyko, Arkady A.; Vahtera, Varpu; Edgecombe, Gregory D. (Zootaxa, 2020)
The extant genera and subgenera of the order Scolopendromorpha are critically reviewed and provided with updated diagnoses and a new identification key; the most recent revisions of scolopendromorph genera are concisely summarised. Rhoda Meinert, 1886 and Cryptops (Chromatanops) Verhoeff, 1906 are suggested to be a junior synonyms of Scolopendropsis Brandt, 1841 and Cryptops (Cryptops) Leach, 1814, respectively. The subgeneric status is formally fixed for Cryptops (Paracryptops) Pocock, 1891 and Cormocephalus (Campylostigmus) Ribaut, 1923; the taxonomic status of the former genus Kanparka Waldock & Edgecombe, 2012 is discussed. As a result of synonymies, the number of scolopendromorph genera and subgenera is currently 37. The formal status of the former tribes Scolopendrini Leach, 1814, Asanadini Verhoeff, 1907 and Arrhabdotini Attems, 1930 is briefly discussed; the presence of the sexual dimorphism among the taxa of generic level is overviewed.